2013
DOI: 10.1016/j.jtcvs.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin and vasopressin influence splanchnic blood flow distribution during and after cardiopulmonary bypass

Abstract: Cardiopulmonary bypass leads to microvascular impairment of jejunal microcirculation, which is associated with the upregulation of endothelin-1 and endothelin subtype A. The administration of vasopressin minimizes these cardiopulmonary bypass-associated alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
(55 reference statements)
3
26
2
Order By: Relevance
“…We assume that in this experiment, vasopressin induced the vasoconstriction within the gastric tissue via arginine vasopressin receptor 1A interaction (AVPR1A) [26]. This finding is in contrast to our previous results demonstrating a protective effect of vasopressin administration on the small bowel microcirculation [7]. …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We assume that in this experiment, vasopressin induced the vasoconstriction within the gastric tissue via arginine vasopressin receptor 1A interaction (AVPR1A) [26]. This finding is in contrast to our previous results demonstrating a protective effect of vasopressin administration on the small bowel microcirculation [7]. …”
Section: Discussionmentioning
confidence: 63%
“…In order to avoid the effects of catecholamines on α- and β-receptors, we chose vasopressin as vasopressor in this experiment. Previously, we have found that the administration of vasopressin diminishes the CPB-induced elevation of endothelin-1 (ET-1) and its receptor subtype A (ET A ), thus preventing CPB-induced jejunal mucosal ischemia [7]. Therefore, in the current study, we investigated whether a similar mechanism is also present in the gastric mucosa, considering that the endothelin system is involved in gastric mucosal ischemia [12].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They theorized that the mechanism behind this phenomenon lies in vasopressin's interaction with arginine vasopressin receptor 1a 18 . However, the same group has shown vasopressin to protect against the impairment of jejunal microcirculatory flow seen with cardiopulmonary bypass through the upregulation of endothelin 19 …”
Section: Enteric Effects Of Pressorsmentioning
confidence: 99%
“…1 In fact, the present publication is just the last addition to a very well-defined scientific excursus the authors have developed in the last years. 2,3 It should be emphasized that despite the fact that NOMI carries a heavy burden of mortality, its existence stays poorly acknowledged, and, as an obvious consequence, NOMI often remains unrecognized and untreated.…”
mentioning
confidence: 99%